Functional geometry of the left ventricle in dilated cardiomyopathy before and after resynchronization therapy - T. V. Chumarnaya; O. E. Solovyova; Yu. S. Alueva; S. P. Mikhailov; O. V. Ostern; V. V. Kochmasheva; O. V. Sopov; A. Sh. Revishvili; V. S. Markhasin (Кардиоваскулярная терапия и профилактика, 2016)
Aim. To analyse quantitative parameters of functional geometry of theleft ventricle (LV) in patients with dilated cardiomyopathy (DCMP), toassess the changes in cardiac resynchronization therapy (CRT) and toreveal the relation of functional geometry of LV and its contractility.Material and methods. In DCMP patients group, who were directed toCRT according to the Guidelines of Russian Arhythmologists Society 2013, echocardiographic study was performed before and after CRT (at 5th day). Based on two-dimensional LV pictures the parameters were assessed in the cycle, as segmented kinetics of wall contraction, LV shape dynamics: sphericity index, Hibson, conicity of apical zone, Fourier shape complexity.Results. In DCMP patients the decrease of global ejection fraction<35% was followed with a decrease of systolic change of all sectoral squares of LV and enhancement of dimensional heterogeneity andasynchronicity of regional wall motion during cardiac cycle comparingto controls. There was negative correlation revealed between theproposed index of non-homogeneity and global ejection fraction. Allshape indexes point to more spherical shape of LV in DCMP. However,opposite to controls, DCMP patients lack dynamical changes ofshape indexes during cardiac cycle, that witnesses on significantdisorders of wall motion coordination in cycle. After CRT there issignificant re-coordination of LV wall motion, followed by restorationof non-homogeneity pattern of segmental kinetics, decrease of nonhomogeneity indexes and of asynchronicity and appearance of thedynamics of shape indexes changes during cardiac cycle. It wasshown that end-systolic indexes of sphericity shape complexity ofFourier make it to separate patients who respond or does not ontherapy, by clinical parameters. Changes of sphericity index betweenend diastole and end systole <3,5% selects patients with the highestprognostic significance comparing with other parameters.Conclusion. Disorders of functional geometry of the LV, particularly anincrease of non-homogeneity and asynchronicity parameters of theregional motion of the wall, decrease of dynamical changes of LVsphericity indexes, might influence contractility and pumping function ofthe heart, and have diagnostic significance in selection of patientsresponding to CRT.